Organizational Communication and Performance of Co-Operative Societies in Uganda. A Case Study of Abateganda Ntungamo Growers Co-Operative Society Ltd - Richards, Arinaitwe (Kabale University, 2022)
A Research Dissertation Submitted to the Directorate of Postgraduate Training in Partial Fulfillment of the Requirements for the Award of Master’s Degree in Business Administration (Management) Of Kabale University